Analisis Pengelolaan Modal Kerja dan Profitabilitas Usaha pada PT Maxis Paragon - Putra, Heri Melvin Sah; Bawamenewi; Hulu, Parlindungan F; Bu’ulolo, Nany Artatina; Harefa, Idarni (Jurnal EMT KITA, 2025)
In the business world, capital and profitability are two crucial factors that affect the sustainability and growth of a company. Capital functions as a resource used to start and run a company's operations. This study aims to measure the level of PT. Maxis Paragon's ability to manage working capital to meet short-term obligations using the liquidity ratio, analyze the level of working capital turnover in operational activities through the activity ratio, and assess the effectiveness of working capital use in generating business profitability using the profitability ratio. The research method used is a quantitative approach with descriptive analysis. The results of the study indicate that the management of PT. Maxis Paragon's working capital during the 2019–2023 period experienced an unhealthy condition based on the analysis of the Current Ratio and Quick Ratio. The company needs to improve working capital management, especially in terms of inventory and receivables management, and identify the causes of the decline in performance in 2023. From an activity ratio perspective, the management of receivables and inventory during this period was considered poor, far below industry standards. Despite improvements in inventory management through 2022, performance declined again in 2023. In addition, profitability ratio analysis shows that the company's profitability, as measured by Net Income and Return on Equity (ROE), is at a low level. To increase returns to shareholders, an in-depth evaluation of the company's operations and financial strategy is needed.